2015
DOI: 10.1002/jsfa.7294
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals determination and classification in purple and red fleshed potato tubers by analytical methods and near infrared spectroscopy

Abstract: The present characterisation of cultivars and breeding lines with high concentrations of phytochemicals is an important step both to support the consideration of specialty potatoes as a source of healthy compounds, and to obtain new cultivars with positive nutritional characteristics. Moreover, by using near infrared spectroscopy a non-destructive identification and classification of samples with different levels of phytochemicals is achieved, offering an unquestionable contribution to the potato industry for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 54 publications
5
26
0
Order By: Relevance
“…High phenotypic correlations between TMA, TSP and HAC in potato have been reported in previous studies (Andre et al., ; Tierno & Ruiz de Galarreta, 2016a; Tierno et al., ). In fact, four major phenolic compounds, including chlorogenic acid, gallic acid, catechin and caffeic acid, account for more than 60%–80% of the total antioxidant capacity in potato (Reddivari, Hale, & Miller, ).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…High phenotypic correlations between TMA, TSP and HAC in potato have been reported in previous studies (Andre et al., ; Tierno & Ruiz de Galarreta, 2016a; Tierno et al., ). In fact, four major phenolic compounds, including chlorogenic acid, gallic acid, catechin and caffeic acid, account for more than 60%–80% of the total antioxidant capacity in potato (Reddivari, Hale, & Miller, ).…”
Section: Discussionsupporting
confidence: 61%
“…The significance of the genotype GCA and SCA interactions with years for all the traits indicated that families responded differently to the year factor. The existence of significant environmental effects and GE for bioactive compounds and antioxidant capacity in tetraploid potato has been previously reported by several authors (Haynes et al, 1996;2000;Tierno et al, 2016). This implies a challenge for breeders as it reduces the correlation between genotype and phenotype.…”
Section: Few Publications Have Dealt With Quantitative Genetics In Rementioning
confidence: 93%
See 1 more Smart Citation
“…Despite the common belief in earlier studies that the most intensely colored yellowfleshed potatoes contained β-carotene, it may be true that there is no β-carotene or just a trace 10 . Rather, Solanum Tierno et al 67 reported variations in the carotenoid concentrations in some colored potato cultivars. There was a six-fold variation in total carotenoids, which ranged from 0.00915 to 0.0590 g/kg FW.…”
Section: Caroteinoidsmentioning
confidence: 99%
“…Recently, NIRS has been mainly used for the determination of potato components (such as potato dry matter, starch, protein, sugar content), evaluation of potato quality (pathology, breed, and grade). [1,[14][15][16][17] Li Xin successfully identified potato varieties and determined their dry matter contents using NIRS. [18] and Norbert U.H.…”
Section: Introductionmentioning
confidence: 99%